PERAN PENDIDIKAN ISLAM DALAM MENUMBUHKAN SIKAP TOLERANSI TERHADAP KEBERAGAMAN BUDAYA DI SEKOLAH DASAR - Ritonga, Masrianti; Fata, Nahriyah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This article aims to examine the role of Islamic education in fostering tolerance towards cultural diversity in elementary schools using a literature study approach. A multicultural society is a group that accepts diversity. Islamic education has a responsibility to instill the values of tolerance, mutual respect, and peaceful coexistence from an early age. This study examines various literature on the concept of tolerance in Islamic teachings, inclusive learning approaches, and the implementation of these values in curriculum and school activities. The results of this study found that Islamic education delivered in a contextual and moderate manner can be an effective means of forming the character of students who are tolerant of cultural, ethnic, and religious differences. In instilling it, maximum support is needed by teachers who have a deep understanding of Islam rahmatan lil 'alamin, as well as a school environment that is conducive to cross-cultural interaction. This study suggests the integration of tolerance values in each learning to strengthen social harmony from an early age.